2012
DOI: 10.1080/15222055.2012.685213
|View full text |Cite
|
Sign up to set email alerts
|

Can Copper‐Based Substrates Be Used to Protect Hatcheries from Invasion by the New Zealand Mudsnail?

Abstract: CAN COPPER-BASED SUBSTRATES BE USED TO PROTECT HATCHERIES FROM INVASION BY THE NEW ZEALAND MUDSNAIL?Aquaculture facilities throughout North America are at risk of invasion by the New Zealand mudsnail (Potamopyrgus antipodarum). Mudsnails can enter facilities in several ways including by crawling through effluent pipes. There is evidence to suggest that lining the insides of these pipes with copper-based substrates to create a contact deterrent could reduce the risk of mudsnail invasion. However, before copper-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…One "disservice" is related to the access restrictions that the authorities impose in NZMS-infested ecosystems (Proctor et al, 2007). Another disservice is the loss of recreational opportunities when stocking of fish from NZMS-positive facilities is limited to infested ecosystems (Hoyer & Myrick, 2012). Both facts prevent the recreational use of certain areas (bathing, fishing, boating, etc.…”
Section: Effects On Cultural Servicesmentioning
confidence: 99%
“…One "disservice" is related to the access restrictions that the authorities impose in NZMS-infested ecosystems (Proctor et al, 2007). Another disservice is the loss of recreational opportunities when stocking of fish from NZMS-positive facilities is limited to infested ecosystems (Hoyer & Myrick, 2012). Both facts prevent the recreational use of certain areas (bathing, fishing, boating, etc.…”
Section: Effects On Cultural Servicesmentioning
confidence: 99%
“…The use of chemosensory alarm cues may present a low cost, non-toxic alternative (Wagner et al, 2011) but their utility for blocking AIS upstream movement has rarely been evaluated in the field, and may not provide the necessary restriction of movement (e.g., Luhring et al, 2016). Using copper as a contact-deterrent substrate barrier shows promise in its ability to block the spread of the invasive New Zealand mudsnail (Potamopyrgus antipodarum; Hoyer and Myrick, 2012). Carbon dioxide barriers can reduce invasive fish passage and can be useful because they do not interfere with shipping and river flow (Cupp et al, 2018).…”
Section: Barrier Typesmentioning
confidence: 99%
“…Three studies were identified that involved the use of barriers to control invasive molluscs: metallic substrates that deterred the dispersal of a gastropod (Hoyer and Myrick, 2012), thermal treatments (hot water immersion) can kill adhered zebra mussels (Dreissena polymorpha) and quagga mussels (Dreissena rostriformis bugensis) on boat hulls as they pass through canal locks (Beyer et al, 2011), and barrier matts that created anoxic conditions to prevent movements of Asian clam (Corbicula fluminea; Wittmann et al, 2012). Only one study investigated the use of barriers to control the spread of amphibians: plastic screens were erected around a pond in Bermuda, effectively preventing invasive cane toad (Rhinella marina) from breeding, resulting in their eradication from an island (Wingate, 2011).…”
Section: Ais Targeted By Exclusion Barriersmentioning
confidence: 99%
“…More rarely, zoophages are used in agriculture: Tetanocera elata (Diptera: Sciomyzidae) (Ahmed et al, 2019) and various species of carabid beetles (Guenay-Greunke et al, 2022). Those methods could be combined with technological means, particularly sowing (Egleton et al, 2021) or creating barriers to hold off mollusks (Schüder et al, 2003;Hoyer & Myrick, 2012).…”
Section: Introductionmentioning
confidence: 99%